Characterisation of Natural Fibre Reinforcements and Composites. (18th December 2013) - Cullen, Richard K.; Singh, Mary Margaret; Summerscales, John
Abstract : Recent EU directives (e.g., ELV and WEEE) have caused some rethinking of the life cycle implications of fibre reinforced polymer matrix composites. Man-made reinforcement fibres have significant ecological implications. One alternative is the use of natural fibres as reinforcements. The principal candidates are bast (plant stem) fibres with flax, hemp, and jute as the current front runners. The work presented here will consider the characterisation of jute fibres and their composites. A novel technique is proposed for the measurement of fibre density. The new rule of mixtures, extended for noncircular cross-section natural fibres, is shown to provide a sensible estimate for the experimentally measured elastic modulus of the composite.